New bird records from the Tempe floodplain lake system, Sulawesi Selatan, and a review of wetland bird and raptor species recorded since 1985 - Andrew Crossland; Ari Wira Sitorus; Andi Sitorus (BIO PALEMBANICA, 2025)
The Tempe floodplain lake system in South Sulawesi is one of Sulawesi’s most important wetland complexes for waterbirds. This paper consolidates records from 1985–2025, including published surveys, eBird data, and new field observations made in November 2023. A total of 69 waterbird and raptor species are now documented for the lake system, with four species newly recorded in 2023. Historical counts contrast sharply with much smaller numbers observed in recent years, suggesting possible population declines. Supplementary evidence from online hunting videos revealed that at least 19 waterbird species are currently targeted by recreational shooters using modern air rifles, highlighting a likely increase in hunting pressure since the 1990s. These findings support earlier concerns about the sustainability of bird harvesting in the Tempe wetlands and indicate a need for renewed monitoring and stronger management of hunting activities. The study demonstrates the value of integrating conventional field data with verified citizen-science and digital media sources to reassess the conservation status of under-studied tropical wetland ecosystems.